Synthesis of multivalent glycoclusters from 1-thio-β-D-galactose and their inhibitory activity against the β-galactosidase from E. coli - Cagnoni, Alejandro (2011)
The synthesis of multivalent glycoclusters, designed to be compatible with biological systems, is reported. A variety of 1-thio-β-d-galactosides linked to a terminal triple bond through oligoethyleneglycol chains of variable lengths has been synthesized. Also, azide-containing oligosaccharide scaffolds were prepared from trehalose, maltose, and maltotriose by direct azidation with NaN3/PPh3/CBr4. Click reaction between the thiogalactoside residues and the azide scaffolds under microwave irradiation afforded a family of glycoclusters containing 1 to 4 residues of 1-thio-β-D-galactose. The yields went from moderate to excellent, depending on the valency of the desired product. Deacetylation with Et 3N/MeOH/H2O led to the final products. Complete characterization of the products was performed by NMR spectroscopy and HR-MS techniques. Their activities as inhibitors of β-galactosidase from E. coli were determined by using the Lineweaver-Burk method. The use of hydrophilic carbohydrate scaffolds for the synthesis of multivalent galactosides represents an interesting approach to improve their pharmacokinetics and bioavailability. In addition, the presence of the thioglycosidic bond will improve their stability in biological fluids.